Negotiations of Blame and Care among HIV‐positive Mothers and Daughters in South Africa's Eastern Cape. (12th March 2017) - Vale, Beth; Hodes, Rebecca; Cluver, Lucie
Abstract: Research delineates two epidemiological categories among HIV‐positive adolescents: those who contract the virus sexually and those who inherit it as infants. In this article, we are interested in how tacit inferences about adolescents' mode of infection contribute to their experiences of HIV‐related blame, and their ability to achieve care, in their intimate, everyday settings. The analysis arises from ethnographic research with 23 HIV‐positive adolescents living in South Africa's Eastern Cape. From these, we draw particularly on the narratives of four HIV‐positive teenage girls and their HIV‐positive mothers. The article explores the social stakes entailed in ascriptions of adolescents' mode of infection, particularly in terms of how blame was allocated between mothers and daughters. It further considers how these families have sought to negotiate repudiation and thereby sustain intergenerational care. The article furthers limited research on the life projects and dilemmas of this HIV‐positive adolescent cohort.